(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In this scientific article, the pedagogical foundations of the organization of football training in military educational institutions were analyzed. Football training manifests itself as an effective tool in the development of physical qualities of cadets, such as physical fitness, coordination, agility and endurance, as well as in the strengthening of psychological stability, the ability to work in a team and discipline. In the research process, methods of pedagogical observation, survey, experimental training and statistical analysis were used. The results showed a significant increase in physical and psychological indicators in cadets, while ensuring military-professional training is possible